The mycorrhizal dependence of subordinates determines the effect of arbuscular mycorrhizal fungi on plant diversity - Urcelay, Roberto Carlos (2003)
It is widely recognized that arbuscular mycorrhizal fungi (AMF) influence plant community structure. Several studies in the past few years have focused on the effect of AMF on plant diversity, showing contradictory results. On the basis of studies carried out in grasslands, it has been proposed that these results may not be in conflict but rather depend on mycorrhizal dependence of dominant and subordinate species in the plant community. Here, we propose a simple conceptual model to explain the effect of AMF on plant diversity and dominance hierarchy. Our model suggests that the effect of AMF on plant diversity can be explained mainly by mycorrhizal dependence of subordinates. It also gives predictions for a wider range of community types, and helps in identifying the systems in which empirical data are most critically needed.